Effect of magnetic graphene oxide on the demulsification process of heavy oil emulsion: article / Nurfarahain Abu Bakar - Abu Bakar, Nurfarahain; Dollah, Aqilah; Othman, Nurhidayati (2019)
The difficulties associated with the crude oil emulsions and produced water cause the oilfield researchers to investigate into practical demulsification methods for many decades. Surfactant is the main component in stabilizing the interfacial film surrounding the dispersed phase droplets which contribute to emulsion stability. The most efficient demulsification method is chemical demulsification which able to attain desirable separation efficiency while complying with the environmental regulations and imposing the least economic burden on the petroleum industry. A magnetic graphene oxide (MGO) was synthesized by one-step co-precipitation method from graphene oxide (GO). The properties of the MGO were characterized by XRD analysis and supported by FTIR analysis. Different concentrations of MGO used to demulsify the heavy oil emulsions of different water cut were studied. The magnetic graphene oxide (MGO) was successfully synthesized and used for separating diluted heavy oil emulsions. Demulsification tests which is bottle test indicated that MGO could separate the emulsions within a few minutes. The residual oil content in the separated water analyzed by UV-Visible spectrophotometer was as low as 20 mg/mL corresponding to a demulsification efficiency of 99.99% at an optimal dosage. The interfacial tension of the emulsions during demulsification process were also analyzed.